Efforts to Develop Cognitive Learning Interest with Interactive Learning Media Based on Crossword Labs in Students at Madrasah Aliyah - Adinda Nur Syafitri; Ainol Ainol; Hawa’ Hidayatul Hikmiyah (Jurnal Pendidikan Indonesia, 2026)
This study aims to develop and analyze the effectiveness of interactive learning media based on Crossword Labs in increasing students' cognitive learning interest at MA. Bahrul Ulum. The background of this study is based on the low interest in cognitive learning of students caused by the use of conventional methods that do not involve active participation and higher-order thinking skills. A qualitative approach was used with a qualitative descriptive research type. The research subjects consisted of subject teachers and students. Data were collected through in-depth interviews, direct observation, and documentation of learning activities through the application of Crossword Labs media. The results showed that the use of Crossword Labs media was able to significantly increase cognitive engagement and student learning interest. Students showed high enthusiasm in solving puzzles related to the subject matter, resulting in an increase in aspects of conceptual understanding and critical thinking skills. In addition, teachers found it easier to manage a more interactive and collaborative learning process. These findings indicate that Crossword Labs media can be an innovative alternative in the development of digital learning media in Islamic high schools, especially in developing the quality of learning that focuses on cognitive learning interest.